Breeding of Soybean (Glycine max (L.) Merrill) for Field Weathering Resistance by Pedigree Method - Phan Thi Thanh; Prapa Sripichitt; Wasana Wongyai; Sunanta Juntakool; Arom Sripichitt (Agriculture and Natural Resources, 2006)
Breeding of soybean for field weathering resistance was conducted by hybridization between commercial variety CM60 which is susceptible to field weathering and two field weathering resistant varieties (GC2796 and SJ1) in 2003. The F1 hybrid plants were grown in the greenhouse at the Department of Agronomy, Kasetsart University and the F2 to F4 progenies were planted in the field at National Corn and Sorghum Research Center, Nakhon Ratchasima province. Field weathering resistance of soybean was evaluated from some seed characteristics involving seed germinability after accelerated aging, seed vigor estimated from the electrical conductivity of seed leachates, percentage of seed coat and seed coat thickness. Selection was done in each succeeding generation from F2 to F4 using pedigree method for plants/lines which had high seed germinability and vigor, high percentage and thickness of seed coat and good agronomic characters. The yield trial of 17 F5 lines was performed at National Corn and Sorghum Research Center in rainy season 2005. Six F5 lines having high seed yield, field weathering resistance and good agronomic characters were selected. These promising lines will be further evaluated for seed yield, field weathering resistance and agronomic performance in different locations.